Nonlinear control for an optimized grid connection system of renewable energy resources - Mohammed El Malah; Abdellfattah Ba-Razzouk; Elhassane Abdelmounim; Mhamed Madark (Bulletin of Electrical Engineering and Informatics, 2021)
This paper proposes an integral backstepping based nonlinear control strategy for a grid connected wind-photovoltaic hybrid system. The proposed control strategy aims at extracting the maximum power available while respecting the grid connection standards. The proposed system has a reduced number of power electronic converters, thereby ensuring lower costs and reduced energy losses, which improves the profitability and efficiency of the hybrid system. The effectiveness of the proposed topology and control methodology is validated using the MATLAB/Simulink software environment. The satisfactory results achieved under various atmospheric conditions and in different operating modes of the hybrid system, confirm the high efficiency of the proposed control strategy.